2021
DOI: 10.1002/marc.202100700
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Effect on Dielectric Properties of Self‐Assembled Polythiourea‐Based Copolymers for Ultrahigh Energy Storage

Abstract: Polymer dielectrics are highly desirable in capacitor applications due to their low cost, high stability, and reliability. However, there still remains a lack of feasible methods to prepare polymer dielectrics with high energy density and low dielectric loss, which severely hampers the development of compact and efficient power electronics. Here, an amphiphilic block copolymer, polythiourea‐b‐polydimethylsiloxane (PTU‐b‐PDMS), with an extraordinarily high energy density of 29.8 J cm−3 and a low loss is synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…A number of novel high T g polymers have been synthesized over the years. Although in some cases the intention is to improve high-temperature energystorage performance, these polymers do exhibit impressive performance at room temperature [132][133][134][135][136][137][138] . Aided by the density functional theory (DFT) computation, a series of polyimide structures were screened for capacitive applications by considering the dielectric constant/loss, bandgap and breakdown strength [132] .…”
Section: Linear Dielectric Polymers and Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of novel high T g polymers have been synthesized over the years. Although in some cases the intention is to improve high-temperature energystorage performance, these polymers do exhibit impressive performance at room temperature [132][133][134][135][136][137][138] . Aided by the density functional theory (DFT) computation, a series of polyimide structures were screened for capacitive applications by considering the dielectric constant/loss, bandgap and breakdown strength [132] .…”
Section: Linear Dielectric Polymers and Compositesmentioning
confidence: 99%
“…The Zhu group showed that incorporation of highly polar sulfonyl groups (-SO 2 ) can significantly improve the dielectric constant and energy density of polymethacrylate and poly(2,6-dimethyl-1,4-phenylene oxide) (PPO) [133,134] . Moreover, Zhang et al reported a novel high-K dipolar glass polymer, denoted as SO 2 -PIMs [136] . The intrinsic microporosity in this material provides large free volume for the rotation of dipolar side groups.…”
Section: Linear Dielectric Polymers and Compositesmentioning
confidence: 99%
“…Abundant studies proved that the electrical breakdown in organic dielectrics under high field was dominated by the trap-dominated charge transport processes. Feng, , Chen, Yuan, , and Li et al reported that a greater trap level in polymers contributed to the repressed charge transport processes, and thus, led to a superior breakdown strength. Therefore, constructing interfacial traps with a higher level in polymers is treated as an effective strategy to fabricate organic dielectrics with greater breakdown strength.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric capacitors supported by the insulating polymerbased dielectrics have been extensively applied in the advanced electronic devices and electric power systems [1][2][3]. In terms of storing electrical energy, attempts have been made to ensure that the polymer-based dielectrics applicable in the capacitors are with excellent energy storage capability, flexibility and processability [4][5][6]. Since popular nanocomposite dielectrics suffer from the drawbacks of poor reproducible, * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%